2015
DOI: 10.1007/s10238-015-0364-3
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose-derived stem cells stimulate neuroregeneration

Abstract: Traumatic brain injuries and degenerative neurological disorders such as Alzheimer's dementia, Parkinson's disease, amyotrophic lateral sclerosis and many others are characterized by loss of brain cells and supporting structures. Restoring microanatomy and function using stem cells is a promising therapeutic approach. Among the many various sources, adipose-derived stem cells (ADSCs) are one of the most easily harvested alternatives, they multiply rapidly, and they demonstrate low immunogenicity with an abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Rodents have an intrinsic ability to effectively regenerate nerves across short gaps; therefore, these experiments do not isolate the benefits of adding adipose tissue from the intrinsic ability of the nerve to regenerate itself. Furthermore, the clinical gold standard for repair of critical peripheral nerve gaps remains nerve autografts, and only one of the experiments evaluated the effectiveness of adipose tissue in supplementing nerve autografts . While this study demonstrated positive histological results, it lacked functional outcome measures.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Rodents have an intrinsic ability to effectively regenerate nerves across short gaps; therefore, these experiments do not isolate the benefits of adding adipose tissue from the intrinsic ability of the nerve to regenerate itself. Furthermore, the clinical gold standard for repair of critical peripheral nerve gaps remains nerve autografts, and only one of the experiments evaluated the effectiveness of adipose tissue in supplementing nerve autografts . While this study demonstrated positive histological results, it lacked functional outcome measures.…”
Section: Discussionmentioning
confidence: 87%
“…Nineteen of the 23 experiments (83%) on cultured undifferentiated ASCs ( cuASCs) demonstrated a significant beneficial effect on nerve regeneration according to their primary outcome measures …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 22 articles were retrieved, all of them experimentally controlled studies in animals. Most studies used rats as host species [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Four studies used mice [16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%